2022
DOI: 10.11591/ijeecs.v26.i3.pp1538-1545
|View full text |Cite
|
Sign up to set email alerts
|

Toward mobile learning at Jordanian higher education institutions

Abstract: Globally, <span>teaching methods and tools in higher education institutions (HEIs) have changed nowadays. Many attempts have been made in Jordanian higher education institutions (JHEIs) in order to improve and continuity of the educational process, especially during coronavirus pandemic. The outbreak of this virus has become a major disruption where all Jordanian universities cancelled classes and moved toward online learning, and mobile learning (ML) has appeared as one of the possible solutions. ML is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The study found that digital skills are absent among students of nursing and the first year of study, which was also reflected in the significantly negative decision to continue this method of learning in higher grades. On the contrary, other study [7] confirmed that the future of education using mobile applications will have a positive effect on student performance as well as interaction in the teaching process [30]. The results indicate the importance of using a digital technology as an educational strategy in the preclinical education of healthcare students, especially in nursing.…”
Section: Evaluating Students' Perceptions Of Digital Concept Mapping ...mentioning
confidence: 87%
See 1 more Smart Citation
“…The study found that digital skills are absent among students of nursing and the first year of study, which was also reflected in the significantly negative decision to continue this method of learning in higher grades. On the contrary, other study [7] confirmed that the future of education using mobile applications will have a positive effect on student performance as well as interaction in the teaching process [30]. The results indicate the importance of using a digital technology as an educational strategy in the preclinical education of healthcare students, especially in nursing.…”
Section: Evaluating Students' Perceptions Of Digital Concept Mapping ...mentioning
confidence: 87%
“…The advantage of digital technologies is that they are not subject to fatigue failure under excessive load of student. Therefore, it is necessary to develop digital skills and critical thinking already during education using appropriate teaching methods [30].…”
Section: Evaluating Students' Perceptions Of Digital Concept Mapping ...mentioning
confidence: 99%
“…To successfully use technology, it was necessary first to figure out what attracted young people to it in the first place (based on the results of a multidisciplinary investigation into the problem) and then capitalize on that (maintaining a proper ratio of learning materials that are both written and visual) [27]. Professionalism and creativity in teaching could motivate students by considering each students' unique characteristics and suggesting challenging and engaging learning activities [28]- [30].…”
Section: Introductionmentioning
confidence: 99%